Reinventing social security worldwide : Back to essentials - Rys, Vladimir (Book collections on Project MUSE., 2010)
In this timely book, the author, with his life-long experience of international social security, advocates reinstating social insurance by reducing the volume of income redistribution, increasing the transparency of money flows and improving citizen information.